Looking north on the Pay Streak, Alaska Yukon Pacific Exposition, Seattle, 1909. - Nowell, Frank H., 1864-1950 (1909)
On verso of photograph: Looking directly up the Pay Streak. In the immediate right is the scenic railway [L.A. Thompson Scenic Railway]. The Igorrote Village can be seen just beyond the white castellated building at the far right of the Pay Streak. View looking almost directly north. PH Coll 727.642 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number